Cardiac function during weaning failure: the role of diastolic dysfunction - Roche-Campo, Ferran; Bedet, Alexandre; Vivier, Emmanuel; Brochard, Laurent; Mekontso Dessap, Armand (Annals of intensive care, 2018)
Background Cardiac dysfunction is a common cause of weaning failure. Weaning shares some similarities with a cardiac stress test and may challenge active phases of the cardiac cycle-like ventricular contractility and relaxation. This study aimed at assessing systolic and diastolic function during the weaning process and scrutinizing their dynamics during weaning trials. Methods Echocardiography was performed during baseline ventilator settings to assess cardiac function at the initiation of the weaning process and at the start and the end of consecutive weaning trials (performed at day-1, day-2, and before extubation if applicable) to explore the evolution of left ventricle contractility and relaxation in a subset of patients. Results Among 67 patients included, weaning was prolonged (≥ 7 days) in 18 (27%) patients and short (< 7 days) in 49 (73%). Prevalence of systolic dysfunction and isolated diastolic dysfunction before the initiation of weaning process were 37 and 17%, respectively. Isolated diastolic dysfunction was more frequent in patients with prolonged weaning as compared to their counterparts. Thirty-one patients were explored by echocardiography during consecutive weaning trials. An increase in filling pressures with an alteration of ventricular relaxation (as assessed by a decrease in tissue Doppler early mitral diastolic wave velocity) was found during failed weaning trials. Conclusions Isolated diastolic dysfunction was associated with a prolongation of weaning. Increased filling pressures with left ventricle relaxation impairment may be a key mechanism of weaning trial failure.